Examining English Language Arts Common Core State Standards Instruction through Cultural Historical Activity Theory - Barrett-Tatum, Jennifer (Education Policy Analysis Archives, 2015)
The English Language Arts Common Core State Standards and corresponding assessments brought about many changes for educators, their literacy instruction, and the literacy learning of their students. This study examined the day-to-day literacy instruction of two primary grade teachers during their first year of full CCSS implementation. Engestrӧm’s Third Generation Cultural Historical Activity Theory is utilized as both a theoretical framework and a method for analysis to provide a rich description of the complex environment in which literacy instruction and learning occur. The ELA standards functioned as the primary objects of literacy instruction and literacy learning activities are discussed within the context of the larger cultural framework where the teachers interpret and implement these standards. Findings from this study illuminate the complex and interrelated influences of ELA CCSS, and reveal the power of the individual teacher in constructing the literacy learning opportunities.